Examining virtue ethical foundations of non-dualistic Vedānta - Raina, Simran; Kumar Tripathi, Varun (Opción, 2019)
Present paper inquires into two issues via comparative research methods; First, non-dualistic Vedanta undertakes any kind of ethical discourse in its philosophical investigations; second, what is the nature of that discourse? The paper demonstrates that the reproaches of life and world denial in the non-dualistic Vedanta are raised primarily from the point of view of normative ethics. As a conclusion, without the proposed understanding of the underpinned virtue ethics in the Non-dualistic Vedānta, the received understanding of the system is incomplete and sustains a misconception that there is no meaningful ethical discourse possible in its framework.